Geometric Range-Free Localization Algorithm Based on Optimal Anchor Node Selection in Wireless Sensor Networks. (10th April 2014) - Woo, Hyunjae; Lee, Chaewoo
In range-free localization scheme of wireless sensor networks, estimating the distance to the anchor nodes having the actual location is common to compute the position of unknown node. Since the range-free scheme is based on the topology information, the accuracy of distance estimation is considerably affected by node density or node deployment. In this paper, we propose a geometric range-free localization algorithm which estimates the unknown positions geometrically by topological information without considering the distance estimation. To achieve this, we propose an optimal anchor node selection algorithm which selects the anchor nodes connected topologically well for the geometrical location estimation. Simulation results show that the proposed algorithm offers considerably an improved performance compared to the other existing studies.